2018
DOI: 10.1002/2017jg004069
|View full text |Cite
|
Sign up to set email alerts
|

Short and Long‐Term Controls on Active Layer and Permafrost Carbon Turnover Across the Arctic

Abstract: Decomposition of soil organic matter (SOM) in permafrost terrain and the production of greenhouse gases is a key factor for understanding climate change‐carbon feedbacks. Previous studies have shown that SOM decomposition is mostly controlled by soil temperature, soil moisture, and carbon‐nitrogen ratio (C:N). However, focus has generally been on site‐specific processes and little is known about variations in the controls on SOM decomposition across Arctic sites. For assessing SOM decomposition, we retrieved 2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
16
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
3
2
1

Relationship

1
5

Authors

Journals

citations
Cited by 25 publications
(19 citation statements)
references
References 84 publications
2
16
0
1
Order By: Relevance
“…Upper permafrost mineral soil samples (<3 %C) from Kylatyk in NE Siberia, incubated at 2 ºC directly after field collection and thawing (measurement after 20-30 hr, following 3 days of pre-incubation), show median C release rates of c. 750 μgC-CO2 gC -1 d -1 (Weiss et al, 2016), compared to c. 1750 μgC-CO2 gC -1 d -1 in the same class of CryoCarb 1-Kolyma samples. Median C release rates in upper permafrost mineral soil samples of the PAGE21 experiment (Faucherre et al, 2018) decrease from c. 170 on day 8 to c. 35 μgC-CO2 gC -1 d -1 on day 343 since start of incubation. It is obvious from these results that there is a rapid decline in C release rates over time of incubation.…”
Section: Discussionmentioning
confidence: 92%
See 4 more Smart Citations
“…Upper permafrost mineral soil samples (<3 %C) from Kylatyk in NE Siberia, incubated at 2 ºC directly after field collection and thawing (measurement after 20-30 hr, following 3 days of pre-incubation), show median C release rates of c. 750 μgC-CO2 gC -1 d -1 (Weiss et al, 2016), compared to c. 1750 μgC-CO2 gC -1 d -1 in the same class of CryoCarb 1-Kolyma samples. Median C release rates in upper permafrost mineral soil samples of the PAGE21 experiment (Faucherre et al, 2018) decrease from c. 170 on day 8 to c. 35 μgC-CO2 gC -1 d -1 on day 343 since start of incubation. It is obvious from these results that there is a rapid decline in C release rates over time of incubation.…”
Section: Discussionmentioning
confidence: 92%
“…displayed a very low C-CO2 production rate per gC. The PAGE21 experiment also revealed that peat samples mineralized a smaller fraction of C over the one year of incubation compared to mineral soil samples (Faucherre et al, 2018).…”
Section: Discussionmentioning
confidence: 94%
See 3 more Smart Citations